2015
DOI: 10.1186/s12885-015-1877-6
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of women’s views on overdiagnosis and screening for thyroid cancer in Korea

Abstract: BackgroundThe incidence of thyroid cancer in Korea has increased by about 25 % every year for the past 10 years. This increase is largely due to a rising incidence in papillary thyroid cancer, which is associated with an overdiagnosis of small tumors that may never become clinically significant. This study was conducted to explore Korean women’s understanding of overdiagnosis and to investigate changes in screening intention in response to overdiagnosis information.MethodsFocus group interviews were conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 15 publications
1
13
0
2
Order By: Relevance
“…Similarly, Park et al revealed that most patients are generally in favor of public screening strategies and that most consider the identification of small‐volume thyroid cancer as potentially lifesaving, which supports widespread use of diagnostic tests to explain the symptoms. Busco et al has proposed that some public concerns regarding the safety and health effects of environmental risk factors, such as nuclear energy, can prompt a spontaneous active surveillance.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Similarly, Park et al revealed that most patients are generally in favor of public screening strategies and that most consider the identification of small‐volume thyroid cancer as potentially lifesaving, which supports widespread use of diagnostic tests to explain the symptoms. Busco et al has proposed that some public concerns regarding the safety and health effects of environmental risk factors, such as nuclear energy, can prompt a spontaneous active surveillance.…”
Section: Introductionmentioning
confidence: 95%
“…In South Korea, primary care physicians frequently own an ultrasound machine 89 and order an ultrasound as an opportunistic screening test during a routine examination. 64 Nagar et al 90 explored the relationship between the age of the physician and incidence of well-differentiated thyroid cancer and found that geographic areas with a high proportion of physicians older than 55 years had a lower increase in incidence compared with areas with a high proportion of physicians younger than 55 years; the correlation was explained by the varying rate of technological adoption. Rosen et al 91 found a correlation between the female sex of the physician and a higher number of imaging studies, suggesting that the style of female physicians is more prone to active searching.…”
Section: Medical Education and Specialtymentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, few patients who undergo cancer screening report discussing overdiagnosis with their physician, and it is likely that even fewer discuss overdiagnosis when they undergo screening for non-cancer conditions such as diabetes 109110. There are challenges to discussing overdiagnosis with patients; the concept may be difficult to understand and some may not recognize overdiagnosis as a real problem 111112. Patients who do appreciate the potential for overdiagnosis may be reluctant to raise concerns with their doctors.…”
Section: Minimizing and Managing Overdiagnosismentioning
confidence: 99%
“…6,7) 한국에서는 국민건강보험공단의 암 검진(National Cancer Screening Program in Korea) 대상에 갑상선 암이 포함되어 있지 않으나, 많은 병원들에서 갑상선 암 검진을 위한 초음 파를 다른 국가에 비해 낮은 가격에 제공하고 있다. 11…”
unclassified